1990
DOI: 10.1111/j.1365-2621.1990.tb03908.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Residual Pink Color in Cooked Turkey Breast and Pork Loin

Abstract: The residual redness was characterized in well cooked meat from turkey breast and pork loin. A simple method of scanning thin slices by transmission spectrophotometry was used to evaluate the meat pigments in situ. Absorption bands at 414, 520, and 550 nm of the spectra obtained from cooked meat led to the conclusion that residual pink color was caused by cytochrome c. The method was further modified to study the effect of air contact on meat color after cooking. Other pigments were spontaneously oxidized as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Numerous etiologies have been described for this pinking in cooked meat (Cornforth et al. 1986; Girard et al. 1990; Ghorpade and Cornforth 1993).…”
Section: Introductionmentioning
confidence: 91%
“…Numerous etiologies have been described for this pinking in cooked meat (Cornforth et al. 1986; Girard et al. 1990; Ghorpade and Cornforth 1993).…”
Section: Introductionmentioning
confidence: 91%
“…The extent of denaturation is dependent on the rate of heating and the end-point temperature of the cooked meat, commonly 68 to 74 °C (7,(9)(10)(11). The red or pink colouration of meats cooked to < 76 °C has been at least partially attributed to undenatured myoglobin (12); pink colouration in meat cooked to higher temperatures has been attributed to myoglobin denaturation and concomitant hemochrome formation (12) and/or to cytochrome c (13). Denaturation of pure myoglobin has been reported to occur at relatively high temperatures, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Redness (+a* value) was not affected by end-point temperature on the top surface (Slice 1) of the sample. Oxidation of pigments could have reduced redness values on the tissue surface (Girard et al, 1990) and masked any effects attributable to end-point temperature. Increasing the end-point temperature from 70 to 80 C reduced redness in Slices 2, 3, and 4, and increasing the end-point temperature from 80 to 90 C reduced redness on the bottom surface (Slice 5).…”
Section: Methodsmentioning
confidence: 99%
“…These products are often marketed without coatings or sauces and color differences are apparent. Girard et al (1990) pointed out that color is a determining factor in acceptance of meat products and Swatland (1983) indicated that meat color is one of the major criteria by which commercial cooking procedures are evaluated.…”
Section: Introductionmentioning
confidence: 99%